Aseptic folliculitis in freshwater and marine fishermen - Junior, Vidal Haddad [UNESP]; Campos, Luana Moraes [UNESP]; Haddad, Gabriela Roncada [UNESP]; Rossetto, Ana Letícia; Rossetto, André Luiz (Maad Rayan Publishing Company, 2020)
Folliculitis is a common skin disease, usually benign, which causes inflammation and eventuainfections of hair follicles. They may have an infectious etiology, mainly due to the bacteria Staphylococcus aureus; it also occurs due to localized irritation, such as in areas of skin friction and for long periods of immersion in water, as in athletes and workers who are continuously exposed to the aquatic environment. Herein, we report on two fishermen, from fluvial and maritime environments, who presented with chronic aseptic folliculitis associated with daily immersion of their lower extremities while exercising the profession and that regressed when there was a decrease in their contact with water.
Keywords: Dermatitis, occupational; Fisheries; Folliculitis; Hair follicle; Skin diseases